Impact of human sepsis on CCCTC-binding factor associated monocyte transcriptional response of Major Histocompatibility Complex II components - Siegler, Benedikt Hermann; Uhle, Florian; Lichtenstern, Christoph; Arens, Christoph; Bartkuhn, Marek; Weigand, Markus A.; Weiterer, Sebastian (PLOS ONE, 2018)
Background Antigen presentation on monocyte surface to T-cells by Major Histocompatibility Complex, Class II (MHC-II) molecules is fundamental for pathogen recognition and efficient host response. Accordingly, loss of Major Histocompatibility Complex, Class II, DR (HLA-DR) surface expression indicates impaired monocyte functionality in patients suffering from sepsis-induced immunosuppression. Besides the impact of Class II Major Histocompatibility Complex Transactivator (CIITA) on MHC-II gene expression, X box-like (XL) sequences have been proposed as further regulatory elements. These elements are bound by the DNA-binding protein CCCTC-Binding Factor (CTCF), a superordinate modulator of gene transcription. Here, we hypothesized a differential interaction of CTCF with the MHC-II locus contributing to an altered monocyte response in immunocompromised septic patients. Methods We collected blood from six patients diagnosed with sepsis and six healthy controls. Flow cytometric analysis was used to identify sepsis-induced immune suppression, while inflammatory cytokine levels in blood were determined via ELISA. Isolation of CD14++ CD16—monocytes was followed by (i) RNA extraction for gene expression analysis and (ii) chromatin immunoprecipitation to assess the distribution of CTCF and chromatin modifications in selected MHC-II regions. Results Compared to healthy controls, CD14++ CD16—monocytes from septic patients with immune suppression displayed an increased binding of CTCF within the MHC-II locus combined with decreased transcription of CIITA gene. In detail, enhanced CTCF enrichment was detected on the intergenic sequence XL9 separating two subregions coding for MHC-II genes. Depending on the relative localisation to XL9, gene expression of both regions was differentially affected in patients with sepsis. Conclusion Our experiments demonstrate for the first time that differential CTCF binding at XL9 is accompanied by uncoupled MHC-II expression as well as transcriptional and epigenetic alterations of the MHC-II regulator CIITA in septic patients. Overall, our findings indicate a sepsis-induced enhancer blockade mediated by variation of CTCF at the intergenic sequence XL9 in altered monocytes during immunosuppression.